Comparative efficacy of intravitreal aflibercept biosimilar QL1207 versus reference aflibercept in the treatment of diabetic macular edema - Zhai, Gaixia; Liu, Na; Wang, Shaopeng; Zhang, Xia (Frontiers in Medicine, 2025)
PurposeThis study aims to comparatively evaluate the clinical efficacy of intravitreal injections of aflibercept biosimilar QL1207 and the reference aflibercept in the treatment of diabetic macular edema (DME).MethodsThis retrospective study analyzed the clinical data of 80 patients (80 eyes) with DME who underwent initial treatment at our hospital’s Department of Ophthalmology between June 2023 and April 2024. Forty patients (40 eyes) received intravitreal injections of the reference aflibercept (aflibercept group). Forty patients (40 eyes) were treated with intravitreal injections of the aflibercept biosimilar QL1207 (QL1207 group). All patients received a 3 + PRN (pro re nata) treatment regimen and completed a minimum follow-up period of 12 months. Best-corrected visual acuity (BCVA), optical coherence tomography (OCT), and optical coherence tomography angiography (OCTA) were assessed before and after treatment. BCVA and central retinal thickness (CRT) were compared between the two groups at baseline and at 1-, 3-, 6-, and 12-month post-treatment. Additionally, the foveal avascular zone (FAZ) area, macular vessel density, the number of intravitreal injections required, and the incidence of adverse reactions were evaluated before and 12 months after treatment.ResultsThe intergroup comparison of BCVA and CRT before and after treatment showed no statistically significant differences (p > 0.05). After treatment, both groups showed significant improvement in BCVA and reduction in CRT compared to pretreatment values (p < 0.05). No statistically significant intergroup differences were observed in the FAZ area, superficial vascular density (SVD), and deep vascular density (DVD) at baseline and 12 months after treatment (p > 0.05 for all comparisons). Following treatment, both groups demonstrated a significant decrease in FAZ area alongside a concurrent increase in SVD and DVD compared to pretreatment values (p < 0.05 for all parameters). During the follow-up period, no statistically significant difference was observed in the number of intravitreal injections administered between the reference aflibercept group (3.58 ± 0.71) and the QL1207 group (3.40 ± 0.63) (p = 0.272). Throughout the follow-up period, no patients developed severe ocular complications, including endophthalmitis, glaucoma, cataract progression, or vitreous hemorrhage. Furthermore, no cardiovascular or cerebrovascular events were reported during the treatment period.ConclusionBoth the reference aflibercept and its biosimilar QL1207 demonstrate comparable efficacy in the treatment of DME, effectively reducing macular edema, improving BCVA, and enhancing macular perfusion status.